Care of Patients Following Cure of Hepatitis C Virus Infection - Terrault, Norah A. (Gastroenterol Hepatol (N Y), 2018)
The vast majority of persons with chronic hepatitis C virus (HCV) infection will achieve virologic cure with the current direct-acting antiviral therapies. Prevention of reinfection is an important aspect of postcure management and key to the elimination of HCV infection globally. Equally important aspects of postcure care are the prevention of liver disease progression and the management of complications in patients who have significant fibrosis at the time of achieving cure. Patients with advanced fibrosis need to remain under surveillance for liver complications, including hepatocellular carcinoma. All patients are potentially at risk for liver disease progression if other factors causing liver injury are present, such as harmful levels of alcohol use or risk factors for fatty liver including obesity, diabetes, and other metabolic comorbidities. Fatty liver is a particular threat to the long-term well-being of patients after HCV cure due to the high prevalence of its risk factors in this population. Strong counseling messages and ongoing monitoring are key.